Determinants of Indonesia’s International Trade: Evidence from an Extended Gravity Model - Dian Fajarini; Ida Budiarty DA; Lies Maria Hamzah (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2026)
The gravity model is widely used to explain international trade flows based on economic size and geographical distance. However, the role of extended variables such as price competitiveness and free trade agreements remains less clear, particularly in developing countries. This study examines the determinants of Indonesia’s international trade using an extended gravity model. Panel data from 38 trading partner countries over the period 2014-2018 are employed. In addition to GDP and distance, this study incorporates the Producer Price Index (PPI) and a free trade agreement (FTA) dummy variable. The model is estimated using a Random Effect Approach. The results show that GDP has a positive and significant effect, while distance has a negative and significant effect on Indonesia’s trade, confirming the relevance of the gravity model. In contrast, PPI does not have a significant effect, and the FTA dummy indicates no significant difference in export performance between partner countries with and without free trade agreements. These findings suggest that variables on traditional gravity model remain more influential than PPI and free trade agreement in explaining Indonesia’s trade patterns